Buccal Fat Pad as a Plastic Surgery Solution for Oroantral Fistula Repair in Maxillofacial Trauma - Ullah, Fahim; Awan, Asadullah; Ishaq, Irfan; Baloch, Masroor Ahmad; Khan, Naveed Ahmad; Khan, Maria Batool; Din, Ekram ud (Journal of Neonatal Surgery, 2025)
Background: An oroantral fistula (OAF) is a pathological void or defect that forms a passage between the maxillary sinus and the oral cavity. This condition arises most commonly due to an extraction of a posterior maxillary tooth or any traumatic event involving the posterior maxilla region. Untreated OAFs can lead to chronic sinusitis, impaired oral function, and other infections. Closure of OAF with buccal fat pad flap has emerged as a simple and reliable technique because BFP is well vascularized supply. To assess the clinical outcomes of using the buccal fat pad flap in the surgical repair of oroantral fistulae, particularly in patients with maxillofacial trauma or extraction-related defects. Methods: A prospective case series was conducted at Burn and plastic surgery center Hayatabad Peshawar from feburary 2023 to October 2024, enrolling 51 patients diagnosed with OAF. After detailed assessment, all patients underwent surgical closure using a pedicled BFP flap. Variables recorded included flap viability, presence of post-operative infection, and fistula closure at three-month follow-up. Associations between patient factors and surgical outcomes were analyzed. Results: The mean age of participants was within the 30–45 year range, with a slight female predominance. Tooth extraction (41.2%) and trauma (35.3%) were the leading causes of OAF. The success rate of fistula closure was 84.3%. Flap viability was maintained in 76.5% of patients, while 19.6% experienced postoperative infection. Flap viability was significantly associated with closure outcome (p < 0.05), whereas smoking and comorbidities were not. Conclusion: The buccal fat pad flap is an effective, minimally invasive solution for closing oroantral fistulae, particularly in trauma-related cases. Its high success rate, low complication profile, and adaptability make it a valuable option in oral and maxillofacial surgical practice.